Prawotwórcza rola orzecznictwa Naczelnego Sądu Administracyjnego w sprawach podatkowych - Małecki, Jerzy (Wydział Prawa i Administracji UAM, 1993)
The problems of "unwritten legal sources" was overlooked in the Polish legal scholarship during the period of real socialism. This was i.a. due to ideological reasons. Currently the assertion that the Supreme Administrative Court makes no law, but only applies the written law is increasingly dubious. The recognition of the law-making role of an administrative court's case-law does not mean that a judge is not bound by the written law. Nonetheless, he is obliged to control tax law from the "lex falsa lex non est" standpoint. The law-making role of the Supreme Administrative Court's case-law takes various forms, which consist i.a. in: the refusal to apply legislative acts in case of their incompatibility with the constitution and/or statutes; enacting precedents; ruling on the validity of the local self-government's tax legislation; the impact of case-law on the practice of applying tax law.
The law-making role of the Supreme Administrative Court's case-law in tax matters